Monitoring Osteoarthritis: A Cross-sectional Survey in General Practice - Clarson, Lorna E. (Libertas Academica, 2013)
BACKGROUND: Despite being a highly prevalent chronic condition managed predominantly in primary care and unlike other chronic conditions, osteoarthritis (OA) care is delivered on an ad hoc basis rather than through routine structured review. Evidence suggests current levels of OA care are suboptimal, but little is known about what general practitioners’ (GPs) consider important in OA care, and, thus, the scope to improve inconsistency or poor practice is, at present, limited. OBJECTIVES: We investigated GPs’ views on and practice of monitoring OA. METHODS: This was a cross-sectional postal survey of 2500 practicing UK GPs randomly selected from the Binley’s database. Respondents were asked if monitoring OA patients was important and how monitoring should be undertaken. RESULTS: Responses were received from 768 GPs of whom 70.8% were male and 89.5% were principals within their practices. Despite 55.4% (n = 405) indicating monitoring patients with OA was important and 78.3% (n = 596) considering GPs the appropriate professionals to monitor OA, only 15.2% (n = 114) did so routinely, and 45% (n = 337) did not monitor any OA patients at all. In total, 61.4% (n = 463) reported that patients should self-monitor. Respondents favored monitoring physical function, pain, and analgesia use over monitoring measures of BMI, self management plans, and exercise advice. CONCLUSIONS: The majority of respondents felt that monitoring OA was important, but this was not reflected in their reported current practice. Much of what they favored for monitoring was in line with published guidance, suggesting provision of suboptimal care does not result from lack of knowledge and interventions to improve OA care must address barriers to GPs engaging in optimal care provision.